Clinical Lectures on Klein and Bion. - Anderson, Robin (Routledge, 1991)
Originally intended as a series of lectures for the general public, outlines the basic ideas of Melanie Klein and Wilfred Bion clearly and directly, and shows these ideas at work in contemporary analysis.